2007
DOI: 10.1002/hipo.20343
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐independent phospholipase A2 influences AMPA‐mediated toxicity of hippocampal slices by regulating the GluR1 subunit in synaptic membranes

Abstract: We have recently documented that phosphorylation of the GluR1 subunit of alpha-amino-3-hydroxy-5-methylisoxazole-propionate (AMPA) glutamate receptors is influenced by calcium-independent forms of phospholipase A(2) (iPLA(2)) activity in the brain. Given the importance of GluR1 subunit phosphorylation in the control of AMPA receptor delivery to synaptic membranes, we tested the influence of iPLA(2) activity on AMPA receptor distribution between neuronal compartments, using organotypic cultured hippocampal slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…NMDA-mediated synaptic plasticity involves efficient AMPA receptor trafficking (Huganir and Nicoll, 2013). However, insertion of GluR1 homomeric receptors in synaptic membranes can lead to AMPA-mediated excitotoxicity (Menard et al, 2007) as GluR2 subunits are recognized to confer calcium impermeability to AMPA receptors (Sommer et al, 1991; Geiger et al, 1995). Strain-related differences in hippocampal learning tasks and regulation of AMPA receptors have been previously reported in mice (Upchurch and Wehner, 1988, 1989; Rossi-Arnaud and Ammassari-Teule, 1998; Menard et al, 2004) but, to our knowledge, not in rats yet.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA-mediated synaptic plasticity involves efficient AMPA receptor trafficking (Huganir and Nicoll, 2013). However, insertion of GluR1 homomeric receptors in synaptic membranes can lead to AMPA-mediated excitotoxicity (Menard et al, 2007) as GluR2 subunits are recognized to confer calcium impermeability to AMPA receptors (Sommer et al, 1991; Geiger et al, 1995). Strain-related differences in hippocampal learning tasks and regulation of AMPA receptors have been previously reported in mice (Upchurch and Wehner, 1988, 1989; Rossi-Arnaud and Ammassari-Teule, 1998; Menard et al, 2004) but, to our knowledge, not in rats yet.…”
Section: Discussionmentioning
confidence: 99%
“…This region was selected because of its vital importance in learning and memory and from prior work that had demonstrated both the abundance of iPLA 2 activity in the hippocampus as well as the impact of pharmacologic inhibition of iPLA 2 on hippocampal function (15,42,43). Furthermore, in the current study, morphologic alterations appeared to be maximally present in the hippocampus (see below).…”
Section: Electrospray Ionization Mass Spectrometric Analyses Of the Hmentioning
confidence: 92%
“…Hence, the reduction of iPLA 2 γ activity, by promoting surface expression of the GluR1 subunit over the GluR2 subunit (which is reflected by a rise in the GluR1/GluR2 ratio in the membrane fraction), could exacerbate excitotoxic cell death through the formation of GluR2-lacking AMPA receptors that would allow adverse Ca2+ influx upon prolonged AMPA receptor activation. Consistent with this possibility, the greater cell death observed under iPLA 2 γ inhibition is prevented by GluR2-lacking AMPA receptor antagonists (Menard et al, 2007). How inhibition of iPLA 2 γ influences the expression of AMPA receptor subtypes in synaptic membranes remains an open question.…”
Section: Ipla 2 and Neuronal Cell Death Mechanismsmentioning
confidence: 90%
“…In addition, recent findings from our laboratory have revealed that constitutive iPLA 2 γ activity might represent an important neuroprotective system capable of limiting brain excitotoxic damage. We have shown that inhibition of iPLA 2 γ by the enantio-specific inhibitor (R)-BEL makes hippocampal slice cultures more vulnerable to AMPA-mediated excitotoxicity (Menard et al, 2007). Overactivation of N-methyl-D-aspartic acid (NMDA) or AMPA glutamatergic receptors, allowing the entry of high cation levels into cells, activates a number of enzymes, including ATPases, lipases, proteases and endonucleases that, in turn, deplete energy stores or damage cell membranes, cytoarchitecture or nucleus, respectively.…”
Section: Ipla 2 and Neuronal Cell Death Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation